Answer:
y-intercept: (0, -2)
x-intercept: (6, 0)
Step-by-step explanation:
The y-intercept is the value of y when x =0. Substitute 0 for x to find the y-intercept.
[tex]3x - 9y = 18[/tex]
[tex]3(0) - 9y = 18[/tex]
[tex] - 9y = 18[/tex]
[tex]y = - 2[/tex]
When x = 0, y = - 2 so the y-intercept is (0, - 2).
The x-intercept is the value of x when y = 0. Substitute 0 for y in the equation to find the x-intercept.
[tex]3x - 9y = 18[/tex]
[tex]3x - 9(0) = 18[/tex]
[tex]3x = 18[/tex]
[tex]x = 6[/tex]
When y = 0, x = 6 so the x-intercept is (6, 0).